TEKNIK SUPERVISI AKADEMIK DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DI SD GUGUS I KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Ketsia F Tumundo (MAP (Jurnal Manajemen dan Administrasi Publik), 2018)
This study aims to describe and analyze the influence of academic supervision techniques by school principals and professional competence on teacher performance in SD Gugus I, West Likupang District, North Minahasa District. The method used in this research is explorative research. The result of this research is applying good learning giving easiness for a teacher to teach and for student in every learning become meaningful and increase student quality. It is suggested to schools to improve the quality of supervision, such as increasing class visits in the context of clinical supervision, observation of improvement, and motivating teacherÔÇÖs spirit at work.